IPSAAS Attributes Dissensions and SMEs Tax Payment Compliance Integrity - Shakirat Adepeju Babatunde (Jurnal Economia, 2023)
AbstractThis study analyses International Public Sector Accounting Standards' effects on the integrity of Small and Medium Enterprises (SMEs) tax payment compliance. This study uses a cross-sectional survey design based on primary data from a questionnaire administration. The sample size is three hundred and nine SMEs. This study employs Descriptive, Pearson Correlation and Multivariate Analysis of Variance (MANOVA) statistical analysis. Findings show that among the tax payment compliance impeding factors are the government's inability to satisfy SMEs in service delivery improvement and developmental goal promise actualisation. SMEs' resistance to pay tax results from a flawed tax dispute resolution system at a severe mitigating significant level. The governance responsiveness through IPSASs attributes dissension contradicts John Locke's social contract doctrine of civil society rights and benefits.  Hence, this study recommends that officeholders should enhance the SMEs' tax payment compliance level. Public officers' approach to governance should reduce taxpayers' exploitation for self-aggrandisement.  Keywords:Tax payment compliance, Integrity, International Public Sector Accounting Standards, Small and Medium Enterprises, Government Responsiveness